Environmental management system and pro-environmental behavior with green marketing mix as a mediator for sustainable industry performance in hotel industry in east Jawa Province, Indonesia - Rainanto, Bambang Hengky (2022)
Tourism is developing and growing the economy, but it also has negative impacts that all parties must be aware of. Increased events such as floods, landslides, decreased water quality, and traffic jams due to tourist vehicles are some examples of the impacts caused by massive development growth, one of which is the tourism sector at the research site in East Java Province, Indonesia. This research is important because the tourism sector is the most effective sector to increase regional income. As one of the main pillars of tourism, the hotel industry needs to make a positive contribution to achieve Sustainable Tourism by reducing negative impacts. To achieve this Sustainable Tourism, the hotel industry needs to apply the principles and attributes that support the creation of Sustainable Industry Performance (SIP). The research question of this research is the extent to which the practice of Environmental Management System (EMS), Pro-Environmental Behavior (PEB), with Green Marketing Mix (GMM) as a mediator to achieve Sustainable Industry Performance (SIP). This study aims to develop a model of the relationship between EMS, PEB, GMM with 17 hypotheses to achieve SIP. The research was conducted using quantitative methods, obtaining data through surveys and processing using SmartPLS version 3. This study involved 206 data from data cleaning, which previously amounted to 228 data. The results of the study found 14 hypotheses were accepted, and three hypotheses were rejected. The results showed that the implementation of EMS had a significant relationship with SIP economic performance and social performance but did not have a relationship with environmental performance. PEB directly has a significant relationship with environmental performance but not with economic performance and social performance. GMM has a significant direct relationship with the three elements of SIP. The study results revealed that GMM became a suitable partial mediator for EMS and PEB to achieve SIP.